Enhanced Biodegradation of Chlorpyrifos by Agricultural Soil Isolate - Farhan, Muhammad; Ali Butt, Zahid; U. Khan, Amin; Wahid, Abdul; Ahmad, Maqsood; Ahmad, Farooq; Kanwal, Amina (Asian Journal of Chemistry, 2014)
Pesticide pollution is increasing day by day and most of them are persistent in environment. In the present study, we isolated microbial strains from cotton growing agricultural soils which are under widespread use of chlorpyrifos (CP). The chlorpyrifos tolerance limit of isolated strains differs significantly from one another. Ct3 (Bacillus cereus) was most resistant and efficient in degrading chlorpyrifos. Number of parameters that affect rate of biodegradation and efficiency were investigated. These parameters include, chlorpyrifos concentration, alternate carbon source, inoculum size and pH. Stain Ct3 was able to utilize chlorpyrifos as carbon and energy source and also show efficient degradation in presence of glucose as alternate carbon source. Enhanced biodegradation in presence of glucose may be due to the rapid increase in number of bacteria. Ct3 was more efficient at pH 8.5 and high inoculum density. However, the recommended inoculum size is 106 cells L-1. Maximum degradation achieved was 88 %, with the initial concentration of 300 mg L-1. The time taken for this was 7 days. This study was successful in chlorpyrifos biodegradation and this can be used for ecological restoration of sites contaminated with chlorpyrifos.